# Math

posted by .

Solve by completing the square

x^2+4x-21=0

Help how do I do this???

• Math -

For this go on to the website discovery education. Then go under students and click math. And then where it says step by step math in green, click on trigonmetry and calculus. I forgot what area of math this is but choose from one of the items. And jot it in the box search thing and when you press enter it gives you the answer with a wonderful explanation on how to get there. I've used it for math a couple of times.

• Math -

x^2+4x-21=0
x^2+4x = 21
take half the middle term coefficient, square it, then add it to both sides

x^2 + 4x + 4 = 21 + 4
(x+2)^2 = 25
x+2 = ± √25 = ± 5
x = -2 ± 5
x = 3 or -7

## Similar Questions

1. ### math,correction

Is this correct now. Problem #1 solve by completing the square. 2x^2+8x+3=0 My answer: x=-2 +/- sqrt (5)/(2) Problem #2 solve by using the quadratic formula 5x^2+3x+1=0 My answer: No solution are defined. You are not completing the …
2. ### Algebra 2

Completing the square method allows you to solve any quadratic equation. For each of the following determine what number completes the square. I cannot find my notes on completing the square, can someone please help with these two …
3. ### math

1. solve by using the quadratic formula. 5x^2+x=3 2. solve by completing the square. x^2=5x+2 3.solve by using the square roots method. 5(x-2)^2=3
4. ### math

i need to solve this equation by completing the square: x^2-14x+1=0 i don't' know how to do this, nor do i know what complete the square means. please help.
5. ### Math

Hi everyone. Would someone be able to help me with this problems?
6. ### math 10

by completing the square method solve the equation. x^2-2x-1 can u factor it?
7. ### Algebra 2

Solve by completing the square. a² - 2√(3a) + 2 = 0 Solve for x. I don't know if you can use completing the square for this problem. ax^n + b = 0
8. ### maths

Consider the equation x(square) + 4px + 2q = 0 where p and q are real constants. a) by completing square, show that (x+2p)square =4P(SQUARE)-2q b) Hence show that x= -2p +/- square root(4 p(square) -2p ) c) Use the above results to …
9. ### Algebra

Which of the following statements is true?